Hydrothermal synthesis of Z-scheme Bi2WO6/Bi2MoO6 heterojunctions for the enhanced photoelectrocatalytic performance of TiO2 NTs: Structure, activity and mechanism approach. (1st May 2023) - Wang, Kesheng; Wang, Qingyao; Zhao, Yuhua; Zhang, Zifeng; Liao, Shengwen; Deng, Yadan; Wang, Xiang; Ye, Qilu
Graphical abstract: Highlights: The Bi2 WO6 /Bi2 MoO6 heterojunctions were synthesized on TiO2 NTs. TiO2 NTs/ Bi2 WO6 -Bi2 MoO6 photoelectrodes displayed the attractive photocatalytic performance. The direct Z-scheme photocatalytic mechanism was explored. Abstract: In this paper, the direct Z-scheme Bi2 WO6 -Bi2 MoO6 heterojunctions were constructed by the simple hydrothermal deposition on TiO2 nanotube arrays (TiO2 NTs). The results revealed Bi2 WO6 /Bi2 MoO6 heterojunctions dramatically enhanced the solar absorption and slowed the electron recombination, which improved the photoelectrocatalytic pollutant removal property, and OH and O2 radicals were the decisive active species. Moreover, the TiO2 NTs/Bi2 WO6 -Bi2 MoO6 photoelectrode exhibited excellent photoelectric conversion and photoelectrocatalytic H2 evolution properties, much higher than the data of TiO2 NTs/Bi2 WO6 and TiO2 NTs/Bi2 MoO6 photoelectrodes. The visible light photoelectrocatalytic H2 evolution rate of TiO2 NTs/Bi2 WO6 -Bi2 MoO6 photoelectrode was 38.03 μmol·h −1 ·cm −2, and it still showed high photocatalytic activity after several experimental cycles. The outstanding photocatalytic activity of TiO2 NTs/Bi2 WO6 -Bi2 MoO6 sample provides a referential template of the Z-scheme heterojunction construction for the application in photocatalytic pollutant removal and H2 evolution.